Perceptions of High School Principals about Teacher Motivation in in the Metropolitan Area of Medellin, 2015 - López-Arellano, Hernán (2017)
This study is an exploratory research with the purpose of measuring perceptions High School principals have about teachers’ motivation in four specific areas: facilities and institutional resources, intrinsic motivation, extrinsic motivation and social impacts. In this article, perceptions of principals working in public and private schools are compared. The authors designed and applied a five Likert-scale questionnaire to determine the perceptions of principals about motivation in their teacher staffs; the tool was implemented in fifty-one schools of the Metropolitan Area of Medellín, Colombia. Data show a higher favorability (i.e., categories with a better score) in private schools than in public ones.